Impoliteness and Gender: An Analysis Of Animation Series Family Guy Season 20th - Fiona Puspitasari Mulyadi; Ratini Setyowati; Rahmaditya Khadifa Abdul Rozzaqwijaya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study examines the use of impoliteness strategies and their relationship with gender in the animated series